Studies on the fundamental properties of cellulosic nanofibers of selected cultivated bamboo species. - Shawkataly, Abdul Khalil (Universiti Sains Malaysia, 2015)
Four selected cultivated bamboo species from Genus Gigantochloa (G. brang, G. levis, G. scortechinii and G. wraYI) were used to investigate their variation of fiber morphology, anatomical structure, chemical composition, thermal behaviour, physical and mechanical properties. Cellulose nanofiber (CNF) was then isolated from all these four species.